A Measurement Plane for Optical Networks to Manage Emergency Events. Issue 6 (2nd November 2017) - Tego, E.; Carciofi, C.; Grazioso, P.; Petrini, V.; Pompei, S.; Matera, F.; Attanasio, V.; Nastri, E.; Restuccia, E.
ABSTRACT: In this work, we show a wide geographical area optical network test bed, adopting the mPlane measurement plane for monitoring its performance and to manage software defined network approaches, with some specific tests and procedures dedicated to respond to disaster events and to support emergency networks. Such a test bed includes FTTX accesses, and it is currently implemented to support future 5G wireless services with slicing procedures based on Carrier Ethernet. The characteristics of this platform have been experimentally tested in the case of a damage-causing link failure and traffic congestion, showing a fast reactions to these disastrous events, allowing the user to recharge the initial QoS parameters.